Andrzej Murzyn, Bogusław Śliwerski, Irlandia. Zielona Wyspa międzykulturowej oraz egalitarnej edukacji i opieki, Oficyna Wydawnicza Impuls, Kraków 2020, ss. 224 - Potulicka, Eugenia (Studia Edukacyjne, 2021)
Recenzja